Clinical and genetic profiles of postnatal patients with skeletal dysplasia in Guangxi during 8 years: a single-center experience - Sheng Yi; Qi Yang; Linlin Wang; Xunzhao Zhou; Shujie Zhang; Jiale Qian; Shang Yi; Jing Huang; Junjie Chen; Qiang Zhang; Fei Chen; Jiao Li; et al. (Orphanet Journal of Rare Diseases, 2026)
Abstract Background Skeletal dysplasia (SD) is a clinically and genetically heterogeneous group of bone and cartilage disorders. Given the typically heterogeneous and nonspecific clinical manifestations associated with these conditions, molecular testing is essential to achieve a definitive diagnosis. To elucidate the clinical and mo l ecular characteristics of genetic skeletal disorders in the Guangxi region, we conducted a retrospective single-center study involving 434 families suspected of having SD who underwent molecular analysis in our department over an eight-year period. We analyzed their clinical and molecular genetic data. Results Among our cohort, facial dysmorphism and short stature emerged as the most prevalent clinical manifestations, followed by growth delay and motor delay. Notably, molecular diagnoses were made at a relatively late age. Our findings revealed a total of 34 chromosomal abnormalities and 265 Mendelian genetic disorders. According to the Nosology of genetic skeletal disorders: 2023 revision, 75 genes were implicated in 199 positive molecular diagnoses, while the remaining 66 positive diagnoses were attributed to 56 causal genes. The most frequently identified causal gene was FGFR3, with the p.G380R substitution being the predominant pathogenic variant. The overall diagnostic yield through whole-exome sequencing was found to be 64.9%. Predictors of a positive molecular finding included short stature, calvaria abnormalities and knee deformities. Furthermore, the molecular diagnostic rate achieved through Sanger sequencing slightly exceeded that obtained via whole-exome sequencing. Conclusions These findings have significantly enhanced the understanding of the clinical and genetic profiles of SD in Guangxi, elucidating the mutation spectrum of the associated causative genes. This study provides valuable clinical experience that can facilitate the effective implementation of genetic testing in the context of SD. Clinical trial number Not applicable